ESRA19-0376 Optimizing post-operative discharge analgesia for patients undergoing major shoulder surgery (rotator cuff repair or shoulder replacement). (30th August 2019) - Sheppard, L; Ford, R
Abstract : Background and aims: At Queen Alexandra Hospital (QAH), there is no local standard for discharge analgesia after major shoulder surgery (MSS). We conducted an initial survey into the variability of analgesia provided on discharge, including differences between weekday and weekend discharges. We investigated how these differences impacted patients' post-operative pain. Methods: Patients were followed up for 5 days post-operatively. Their discharge analgesia and compliance were recorded. Patients reported their Wessex Pain Score (a 0–3 pain scale increasing in severity) and whether they accessed out of hour services to acquire additional analgesia to that provided on discharge. Results: 20 patients were surveyed, selected consecutively between weekday and weekend discharges. At day five 8/10 weekday patients were still using at least one weak opiate, compared to 4/10 weekend patients. The average 5-day pain score for weekend patients was 2.165 and 1.866 for weekday patients. Two patients accessed out of hours services for additional analgesia; both were weekend discharges. The 5-day average pain scores for weekday vs. weekend rotator cuff repairs and shoulder replacements were 2.0825 vs. 2.096 and 1.722 vs. 2.61, respectively. Conclusions: This survey suggests that weekend discharges of MSS at QAH experience more post-operative pain, particularly for shoulder replacements. It is also pertinent that both groups were still experiencing considerable pain at day 5. To reduce unwarranted variation in discharge analgesia and improve overall pain management, a post-operative analgesia timetable specific to MSS patients was developed. This will be trialed in the coming months and audited to measure its effectiveness.